Aleutian Cackling Goose Branta hutchinsii leucopareia use of pastures in relation to livestock management - Spragens, Kyle M.; Black, Jeffrey M.; Johnson, Matthew D. (Wildfowl, 2015)
The recovered Aleutian Cackling Goose Branta hutchinsii leucopareia population nowadaysÂ relies during spring on livestock-grazed pastures along the coast of Humboldt and DelÂ Norte Counties, northern California, USA. Selection of these foraging sites has howeverÂ put geese in direct competition with livestock, which in turn has led to increased actionsÂ to reduce economic impacts to local farmers. We assessed forage characteristics betweenÂ the two primary livestock grazing regimes that shape this landscape of beef cattleÂ ranches and dairy cow farms. Peak counts and densities of Aleutian Cackling Geese wereÂ associated with the chronology of highest crude protein concentrations and low forageÂ heights, but the timing did not coincide with greatest spatial distribution of use acrossÂ this staging area. Grass crude protein concentrations peaked in February and wereÂ generally higher in dairy pastures than in beef pastures. However, use of dairy pasturesÂ was not observed until a month after staging commenced in this region. We encourageÂ wildlife land managers to provide a successional range of short sward high proteinÂ pasture, by improving areas subject to invasion by salt tolerant plants, low in digestibility,Â in the coastal region and by irrigation in the uplands. These two mechanisms are likely toÂ deliver more grassland of better quality for Aleutian Geese, and to encompass temporalÂ and spatial shifts that occur on this landscape throughout the spring staging period.